PRACTICAL LAW DEVELOPMENT THE INSTITUTION OF POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS TO ACHIEVE THE VALUE OF JUSTICE - Suci, Ivida Dewi Amrih; Poesoko, Herowati; Raharja, Sunarya; Puryani, Puji; Andani, Devi (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Practical law development is described as implementing the duties or ideals of the law in practice. Law is an arrangement the state provides to the community as a guarantee of security for justice seekers (justiabelen). In practice, cases examined in the application of the law by linking the regulatory norms with the legal facts, then the result of the judge's analysis is the ratio decidendi as the basis for making the ruling, as well as the decision in the PKPU realm in bankruptcy law which is lex specialist on the work of PKPU institutions. The success of the PKPU institution's work with a court decision that has permanent legal force (inkracht van gewijsde) (vide Article 287 of the Bankruptcy and PKPU Law). The PKPU peace institution in every case settlement is needed to be strongly encouraged so that the success rate is high. This is because this institution at an early stage is desired to be a tool in stopping the bankruptcy decision for the debtor, so that the debtor can continue his business and can pay his debts to creditors, therefore it is expected to provide justice for the parties who are litigating. The purpose of law is to achieve the value of justice, with the value of legal certainty and the value of the benefits of the PKPU institution, which is part of the value of justice as a legal goal. The author in this article analyzes